Composite bottlebrush mechanics: α-internexin fine-tunes neurofilament network properties1. Issue 29 (7th August 2015) - Kornreich, M.; Malka-Gibor, E.; Laser-Azogui, A.; Doron, O.; Herrmann, H.; Beck, R.
<x xml:space="preserve">Abstract</x> We measure the mechano-elastic properties of composite bottlebrush nematic hydrogels consisting of proteins originated from the central nervous system. We show that intra-brush interactions fine-tunes the network structure which may serve as a structural-regulatory mechanism in neuronal early developmental stages.